A study on diagnosis and management of arteriovenous malformation of uterus - Patel, Nidhi B.; Shah, Sapana R.; Parikh, Purvi M.; Chudasama, Tanmay J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Arteriovenous malformation is abnormal connection between an organ’s arterial and venous circulation. In acquired AVM, history of uterine procedure seems inevitable. Their clinical feature is usually vaginal bleeding. It is diagnosed by 2-D ultrasonography combined with colour doppler. Most of the time they resolve spontaneously; however, if left untreated, uterine artery embolization or hysterectomy comes in hand. The purpose of this study was to evaluate the role of TVUS and colour doppler in the diagnosis and follow-up of treated cases of uterine AVM. This study also aims to evaluate different modalities to manage uterine AVM. Methods: This was a retrospective study done at tertiary care centre from January 2018 to December 2019 to assess the presentation, treatment, and clinical pictures of patients with uterine AVM that were diagnosed with TVUS. Authors reviewed both (1) clinical data (2) ultrasound data of patients. The diagnostic criteria were “subjective” with a rich vascular network in the myometrium with the use of colour Doppler images and “objective” with a high PSV of 20 cm/sec in the vascular web. Results: Thirteen patients met the diagnostic criteria mentioned above. Out of that 100% presented with on and off bleeding per vaginum. Recent and remote history of uterine procedures were in found in 84.6% (n=11) of cases. UAE was done in 53.8% (n=7) cases. Thirty-three (33%) (n=5) cases spontaneously resolved when closely monitored with serial imaging and serum beta- HCG levels. Hysterectomy was needed in 7.4% (n=1) of patients of AVM. Conclusions: Uterine AVM occurred after unsuccessful pregnancies or uterine procedures. Triage of patients for expectant treatment, hormonal treatment vs intervention with uterine artery embolization based on their clinical status, which was supplemented by objective measurements of blood velocity measurement in the AVM, appears to be a good predictor of outcome.